Experimental Evaluation of a System to Control the Incremental Forming of Aluminum Alloy Type 1050 - Ghazi, Safaa Kadhim; Salloom, Maher Yahya; Bedan, Aqeel Sabree (Engineering, Technology & Applied Science Research, 2024)
The hybrid method, known as Incremental Sheet Hydro Forming (ISHF), is a combination of the techniques of Incremental Sheet Forming and Sheet Hydro-Forming. The primary concern identified in the incremental sheet forming formation strategy relates to the potential failure of the product due to the thinning of the sheet and subsequent springback. In response to the issue of sheet failure resulting from thinning, a revised iteration of the integrated sheet hydroforming (ISHF) method was proposed. The revised version of the ISHF process has demonstrated notable improvements in the malleability of the material. The ISHF technique entails the movement of a single ball tool along one side of the sheet's surface, while hydraulic support is applied on the opposite side through the use of pressurized hydraulic fluid. The present study sought to investigate the impact of hydraulic support on metal formability and thickness distribution. In addition, a modified variant was also considered. The experimental results are in close agreement with the predictions made by the analytical models. The strain distribution throughout the length of deformation for the sheet has been calculated. The surface quality of the products was found to be satisfactory and a preliminary simulation has been performed. This study examines the influence of process factors, specifically spindle speed (1000/1500/2000 RPM), feed rate (400/600/800 mm/min), tool diameter (8/10/12 mm), and step-down (0.2/0.4/0.6 mm), on the cone-shaped feature at the specimen of aluminum alloy A 5010. The results demonstrated that, through analysis of variance, the most influential factor in the distribution of thickness was speed. Regarding formability, the rate of change was found to be the highest at 50%.